(untitled) (Fiep Bulletin - online, 2011)
This present article focuses the 2nd Adulthood project: University of the Quality of Life, made possible since 2004 at Physical Education Faculty at Amazon Federal University through the Nucleus of Integrated Studies of the Adult’s Development (NEIDA – FEF – UFAM) The project uses of the tripod Physical Activity, Nutrition, and Mental Health with tack results the systemize physical activity.